A new species of Antocha Osten Sacken, 1860 (Diptera: Limoniidae) from Sichuan, China - Markevičiūtė, Radvilė; Podenas, Sigitas; Saldaitis, Aidas; Bernotienė, Rasa (Zootaxa, 2019)
The short-palped crane fly, Antocha (Antocha) bella Markevičiūtė & Podenas sp. nov., is described from specimens collected in Sichuan, China. Redescriptions of Antocha (Antocha) fortidens Alexander, 1933 and Antocha (Antocha) nebulipennis immaculata Alexander, 1938, illustrations of distinguishing morphological features, general distribution, checklist and key to species of Antocha Osten Sacken from Sichuan, China are provided.